The Effect of Bariatric Surgery on Circulating Levels of Oxidized Low-Density Lipoproteins Is Apparently Independent of Changes in Body Mass Index: A Systematic Review and Meta-Analysis. (6th December 2021) - Jamialahmadi, Tannaz; Reiner, Željko; Alidadi, Mona; Kroh, Matthew; Cardenia, Vladimiro; Xu, Suowen; Al-Rasadi, Khalid; Santos, Raul D.; Sahebkar, Amirhossein
Abstract : Background . Obesity is related to dyslipidemia and increased circulating oxidated LDL (ox-LDL) concentrations that may predispose to atherosclerosis. Bariatric surgery may lower the risk of cardiovascular mortality. Elevated plasma ox-LDL has been associated with atherogenesis and atherosclerotic cardiovascular disease (ASCVD) events. The aim of this meta-analysis was to investigate the impact of bariatric surgery on proatherogenic circulating ox-LDL levels in patients with severe obesity. Methods . Four databases were systematically searched from inception to May 1, 2021. Also, to clarify the heterogeneity of studies with regard to treatment duration, research design, and the demographic features, a random-effects model and the generic inverse variance weighting approach were utilized. To determine the association with the estimated effect size, a random-effect meta-regression approach was performed. Finally, a meta-regression analysis was conducted to explore the influence of, respectively, baseline and changes in body mass index (BMI), baseline ox-LDL, and postsurgery follow-up period with the estimated effect size of surgery on ox-LDL levels. Results . Meta-analysis of 11 studies including 470 subjects showed a significant decline in circulating ox-LDL following bariatric surgery (SMD: -0.971, 95% CI: -1.317, -0.626, p < 0.001, I 2 : 89.43%). The results of meta-regression did not show any significant association between the changes in ox-LDL after bariatric surgery and baseline BMI, duration of follow-up or baseline ox-LDL values. However, there was a significant association between ox-LDL alteration and percentage of BMI change. Conclusion . Bariatric surgery in patients who had severe obesity causes a decrease of circulating ox-LDL that was apparently dependent in BMI changes.